INTEGRASI ISLAM DAN SAINS PADA MATA PELAJARAN BIOLOGI KELAS XII MADRASAH ALIYAH KURIKULUM 2013 - Fajar Mahfiroh; Muhammad Munadi (Jurnal Al-Fatih, 2021)
From the perspective of the ulumul Qur'an, the verses of Allah are actually divided into two, namely the kauniyah verse and the qauliyah verse. The qauliyah verse is God's verse contained in the Qur'an while the kauniyah verse is God in the form of the universe. In the Qauliyah verse Allah also tells a lot about the universe. In order to address these problems, it is necessary to have the concept of integration between religion and science in the world of Islamic education. This study discusses the offer of the concept of integration of Islam and science, especially in biology class XII Madrasah 'Aliyah Curriculum 2013. This research is library research, using a descriptive approach method. The data used were obtained from primary data in the form of the Qur'an and its interpretation as well as biology module class XII Madrasah 'Aliyah Curriculum 2013. While secondary sources in the form of literature that supports primary sources. The method of data collection using the documentation method, in the form of the Qur'an and its interpretation as well as other relevant references. The validity of the data used is construct validity and content validity. Furthermore, data analysis using Content analysis. The results of this study indicate that there are 33 verses in the Qur'an that discuss biology with material on growth and development, human heredity, and evolution.